High-Flow Nasal Cannula Oxygen in Patients Having Anesthesia for Advanced Esophagogastroduodenoscopy: HIFLOW-ENDO, a Randomized Clinical Trial. (7th May 2020) - Mazzeffi, Michael A.; Petrick, Kendra M.; Magder, Laurence; Greenwald, Bruce D.; Darwin, Peter; Goldberg, Eric M.; Bigeleisen, Paul; Chow, Jonathan H.; Anders, Megan; Boyd, Cynthia M.; Kaplowitz, Jeremy S.; Sun, Kai; et al.
Abstract : BACKGROUND: Over 6 million esophagogastroduodenoscopy (EGD) procedures are performed in the United States each year. Patients having anesthesia for advanced EGD procedures, such as interventional procedures, are at high risk for hypoxemia. METHODS: Our primary study aim was to evaluate whether high-flow nasal cannula (HFNC) oxygen reduces the incidence of hypoxemia during anesthesia for advanced EGD. Secondarily, we studied whether HFNC oxygen reduces hypercarbia or hypotension. After obtaining written informed consent, adults having anesthesia for advanced EGD, expected to last longer than 15 minutes, were randomly assigned to receive HFNC oxygen or standard nasal cannula (SNC) oxygen. The primary outcome was occurrence of one or more hypoxemia events during anesthesia, defined by arterial oxygen saturation <92% for at least 15 consecutive seconds. Secondary outcomes were occurrence of one or more hypercarbia or hypotension events. A hypercarbia event was defined by a transcutaneous CO2 measurement 20 mm Hg or more above baseline, and a hypotension event was defined by a mean arterial blood pressure measurement 25% or more below baseline. RESULTS: Two hundred seventy-one adult patients were enrolled and randomized, and 262 patients completed study procedures. Eight randomized patients did not complete study procedures due to changes in their anesthesia or endoscopy plan. One patient was excluded from analysis because their procedure was aborted after 1 minute. Patients who received HFNC oxygen (N = 132) had a significantly lower incidence of hypoxemia than those who received SNC oxygen (N = 130; 21.2% vs 33.1%; hazard ratio [HR] = 0.59 [95% confidence interval CI, 0.36–0.95]; P = .03). There was no difference in the incidence of hypercarbia or hypotension between the groups. The HR for hypercarbia with HFNC oxygen was 1.29 (95% CI, 0.89–1.88; P = .17), and the HR for hypotension was 1.25 (95% CI, 0.86–1.82; P = .25). CONCLUSIONS: HFNC oxygen reduces the incidence of hypoxemia during anesthesia for advanced EGD and may offer an opportunity to enhance patient safety during these procedures.